Tourism in promoting economic growth the case of Baler, Aurora - Angeles, Aaron Gonzales; Montera, Krisel Mendoza (2012)
In the past few decades, tourism was recognized as a good development strategy in the third world countries. It is able to immediately address the primary problem on income and employment. Furthermore, tourism is also a good approach in increasing foreign exchange, addressing poverty alleviation, and contributing to wages, gross operating surplus, taxes and GDP. The purpose of the study is to look into how tourism in Baler promotes economic growth. The study identified the contributions of the tourism to employment. A comparison of the agriculture sector and the tourism sector in terms of employment and income generation was also employed to provide a view as to why tourism is the development strategy adapted by the local government of Baler. Furthermore, this study also assessed the prospects from the local government to further boost their local economy whole maintaining a sustainable development. The study found out that tourism brought about an increase in the employment as well as income level given the various tourism-related opportunities present which include both direct and indirect. Agriculture sector in comparison to the tourism sector, although the primary source of income and employment in Baler, is becoming secondary of terms of the overall economic contribution to the local economy of Baler. The biggest portion of the total revenue of the government is attributed to tourism and the different opportunities it creates. The success of tourism in promoting and boosting the local economy of Baler has to do with the projects and programs of the government and through the active participation of both the private sector and the citizens. Future development plans of the government are pointing towards a sustainable ecotourism development which is favorable to all of the stakeholders. Although, it should follow a stricter implementation with increased budget allocation as to ensure that all the parties involved will benefit given that the present programs and projects of the government is being disadvantageous especially to the poor due to the lack of viable alternatives for their livelihood. The present programs and projects of the government are good in so far as providing alternative livelihood to the poor. However, the problem is the viability of the feasibility of such programs as it appears in our study that the target of these livelihood programs are unable to avail or participate given that there are financial costs involved -- Author's abstract.